Penerapan Media Book Creator Untuk Meningkatkan Kreativitas Menulis Teks Pidato Persuasif pada Siswa Kelas VIII.3 di SMP Pupuk Kujang - Dedi Soepandi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study examines the use of Book Creator in increasing creativity in writing persuasive speeches for grade VIII.3 students at SMP Pupuk Kujang. The researcher implemented PTK (Classroom Action Research) through several steps, including (1) identifying stages in increasing creativity in writing persuasive speeches using Book Creator in grade VIII.3 students at SMP Pupuk Kujang, (2) carrying out measurements related to increasing student creativity in writing persuasive speeches using Book Creator in grade VIII.3 students, and (3) collecting student responses to the use of Book Creator in supporting creativity write their persuasive speeches. Students in grade VIII.3 are designated as research subjects, and data is collected through questionnaires, interviews, observations, and tests. The results of the descriptive-analytic analysis showed that: (1) the teaching process conducted by the teacher was effective, (2) the use of Book Creator media effectively improves students' ability to write persuasive speeches, as evidenced by the increase in the average classical score from 64.28 in the first cycle to 85.14 in the second cycle, and (3) students' reactions to using Book Creator in the classroom were favorable.